Thucydides' Pentekontaetia and Other Essays - Pritchett, W. K., (Archaia Hellas ;, 1995)
In this book Professor Pritchett offers five original essays under the titles: Thucydides' Pentekontaetia; Thucydides 1.61.3-5; Diodoros' Pentekontaetia; The Solar Year of Thucydides; Aetiology sans Topography. The initial lengthy essay focuses on seven crux passages in which Thucydides in Book 1 describes the growth of Athenian power, maintaining against recent critics that they are presented in chronological order. The study combines a review of the manuscript tradition with regard to corruptions in toponyms and numerals and a personal autopsy of the ancient sites. In a separate essay, Pritchett adduces new arguments in defense of Thucydides' seasonal chronological scheme. In the last essay, he takes sharp issue with a recent publication which attempts to attribute the origin of the ancient accounts of the Messenian wars and the battles of Hysiai, Thyreatis, and Phigaleia to legends evolved at festivals.